KCNQ1OT1 promotes ovarian cancer progression via modulating MIR‐142‐5p/CAPN10 axis - Liu, Hongli (Mol Genet Genomic Med, 2020)
BACKGROUND: Long non‐coding RNA (lncRNA) has been regarded as crucial regulator for cancer progression. Roles of KCNQ1 opposite strand/antisense transcript 1 (KCNQ1OT1) in cancers including osteosarcoma and colon cancer have been previously reported. However, its role in ovarian cancer (OC) remains unclear. METHODS: Expression level of KCNQ1OT1 on OC cells and normal cell was analyzed with quantitative real‐time PCR. Gain and loss‐of‐function experiments were performed to analyze the biological roles of KCNQ1OT1 in OC. Moreover, whether KCNQ1OT1 functions its role via mediating MICRORNA‐142‐5p (MIR‐142‐5p)/calpain 10 (CAPN10) axis was analyzed. In addition, effects of KCNQ1OT1, MIR‐142‐5p, and CAPN10 on overall survival of OC patients were analyzed at Kaplan–Meier plotter website. RESULTS: We showed KCNQ1OT1 was elevated expression in OC cells and indicated poorer overall survival of OC patients. Besides, we found KCNQ1OT1 could promote OC cell proliferation and migration in vitro. Moreover, MIR‐142‐5p was found reduced expression, while CAPN10 was found elevated expression in OC cells compared with normal cell. Kaplan–Meier curve analysis showed low MIR‐142‐5p or high CAPN10 expression were indicators for poorer overall survival of OC patients. At length, we showed KCNQ1OT1 could regulate OC development via MIR‐142‐5p/CAPN10 axis. CONCLUSIONS: Taken together, KCNQ1OT1 upregulates CAPN10 expression via sponging MIR‐142‐5p, thus promoting the proliferation and migration of OC.